2019
DOI: 10.1029/2018jd029503
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Midlatitude Heavy Precipitation to SST: A Case Study in the Sea of Japan Area on 9 August 2013

Abstract: This study investigates the influence of sea surface temperature (SST) over the Sea of Japan on a heavy precipitation event that occurred over the northern part (Northern Tohoku region) of Japan's largest island on 9 August 2013. Sensitivity experiments with the Weather Research and Forecasting model show that warmer (cooler) SSTs prescribed over the Sea of Japan in the simulations lead to an increase (decrease) in 24‐hr precipitation averaged within the Northern Tohoku region, especially on the Sea of Japan (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 38 publications
(57 reference statements)
3
18
0
Order By: Relevance
“…Episodes involving ≥ 100 mm in 24 h are more frequent but sometimes have no direct impact or quite a negligible effect, because other factors are the main drivers of floods, e.g. precipitation duration (Jang, 2015), initial soil moisture conditions and hydrological parameters (Norbiato et al, 2008;Martina et al, 2009). Furthermore, the area affected by episodes of ≥ 100 mm in 24 h is sometimes local and is therefore not easily associated with advective synoptic patterns (Gilabert and Llasat, 2018).…”
Section: Selection Of Torrential Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Episodes involving ≥ 100 mm in 24 h are more frequent but sometimes have no direct impact or quite a negligible effect, because other factors are the main drivers of floods, e.g. precipitation duration (Jang, 2015), initial soil moisture conditions and hydrological parameters (Norbiato et al, 2008;Martina et al, 2009). Furthermore, the area affected by episodes of ≥ 100 mm in 24 h is sometimes local and is therefore not easily associated with advective synoptic patterns (Gilabert and Llasat, 2018).…”
Section: Selection Of Torrential Eventsmentioning
confidence: 99%
“…Seawater constitutes an energy store, i.e. recharge areas, which can influence water vapour content and can intensify precipitation episodes (Pastor et al, 2018;Iizuka and Nakamura, 2019) by means of a sea-atmosphere moisture exchange. Furthermore, a significant release of latent heat occurs during atmospheric convection over a warm sea like the Mediterranean at the end of summer and the beginning of autumn (Pastor et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Particular attention has been devoted to the role that SST structures have on heavy precipitation events in the Mediterranean, where widespread coastal urbanisation leads to large exposure of population and infrastructure to intense weather events. While the total amount of rain is not influenced much by the spatial resolution of the SST forcing field (Millán et al ., ; Pastor et al ., ; Lebeaupin et al ., ; Cassola et al ., ), numerical studies show that the spatial structure of the heat fluxes and the position of the rain bands can be influenced (Katsafados et al ., ; Ricchi et al ., ; Rainaud et al ., ; Meroni et al ., ; Iizuka and Nakamura, ). The landward moisture fluxes can also be influenced by the mesoscale SST structures on seasonal scales, as shown by the numerical work of Desbiolles et al .…”
Section: Introductionmentioning
confidence: 98%
“…Recent studies have shown that the midlatitude ocean, especially the Kuroshio Current, is critical to the occurrence of heavy rainfall events around Japan (Miyama et al 2012;Manda et al 2014;Iizuka and Nakamura 2019;Sekizawa et al 2019;Yamamoto 2020). Miyama et al (2012) examined a convective rainband that developed along the Kuroshio Current over the East China Sea in May 2010 and found that the high sea surface temperature (SST) of the Kuroshio Current intensified the rainband by decreasing static stability.…”
Section: Introductionmentioning
confidence: 99%